Analysis of the Influence of Papaya Seed Coffe Quality on Purchase Interrest in Purchase: Analisis Pengaruh Mutu Kopi Biji Buah Pepaya Terhadap Minat Beli Masyarakat - Kurnia Sari, Risca; Mondiana, Yani Quarta; Utama, Satria Putra (Universitas Muhammadiyah Sidoarjo, 2022)
The large amount of wasted papaya seed waste attracted the interest of researchers to investigate further so that what was previously in the form of waste disposed of by the community could be utilized as well as possible and could be of more economic value. This study uses the type of research Explanatory Research. The survey method was used in this study. Data analysis in this study used the SPSS approach. The sample used was 75 students in the city of Malang. The results showed that papaya seeds are not only a waste but also have benefits as coffee that can be used as an alternative to caffeinated coffee. Papaya fruit seeds that are used as coffee have economic value because they can be sold, data analysis shows that the quality of papaya fruit coffee has a positive effect on intens to buy.